Carbon dioxide hydrogenation to methanol catalyst, preparation method and application thereof
Patent Information
- Application Number
- CN202510974888.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-07-15
AI Technical Summary
[0004]本发明的目的是为了克服现有技术存在的如何同时提高二氧化碳加氢催化剂的CO2转化率和甲醇选择性等问题,提供一种二氧化碳加氢制甲醇催化剂及其制备方法和应用,该二氧化碳加氢制甲醇催化剂中含有铜锌双金属氧化物以及采用氮掺杂的碳材料对铜锌双金属氧化物进行修饰,从而可以使得该二氧化碳加氢制甲醇催化剂的催化活性和甲醇选择性显著提升
[0020] The carbon dioxide hydrogenation to methanol catalyst of this invention modifies a copper-zinc bimetallic oxide using nitrogen-doped carbon material. This nitrogen-doped carbon material modulates the electronic structure of the copper-zinc bimetallic oxide, promoting not only the formation of the Cu/ZnO interface but also enhancing the interaction between Cu and ZnO, which is beneficial for methanol production. This results in a significant breakthrough in the activity of the carbon dioxide hydrogenation to methanol catalyst, exhibiting both high CO2 conversion and high methanol selectivity, thus solving the technical challenges currently faced by Cu/ZnO catalysts.
Smart Images

Figure CN120695872B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of heterogeneous catalysis technology, specifically to a catalyst for the hydrogenation of carbon dioxide to methanol, its preparation method, and its application. Background Technology
[0002] Excessive emissions of greenhouse gases, primarily CO2, contribute to the greenhouse effect and global warming. Methanol is not only an important chemical raw material but also a high-performance energy carrier. Therefore, the coupling of CO2 with green hydrogen to produce methanol can not only solve CO2 emission problems but also partially meet human needs for fuels and chemicals, truly achieving green carbon utilization and sustainable recycling.
[0003] Cu / ZnO catalysts are one of the mainstream catalysts for the hydrogenation of CO2 to methanol. However, at lower reaction temperatures, the single-pass CO2 conversion rate is low. Increasing the temperature helps improve the CO2 conversion rate, but it leads to a rapid decrease in the methanol selectivity of the Cu / ZnO catalyst. The optimal conditions are: pressure 3-5 MPa, CO2:H2 = 1:3, reaction temperature 220℃-300℃, and volume hourly space velocity 3000-50000 h⁻¹. -1 Under these conditions, the CO2 conversion rate is approximately 10%-18%, while the methanol selectivity remains at 40%-70%. Therefore, how to simultaneously improve the CO2 conversion rate and methanol selectivity of current carbon dioxide hydrogenation catalysts is a key bottleneck problem that urgently needs to be solved. Summary of the Invention
[0004] The purpose of this invention is to overcome the problems existing in the prior art regarding how to simultaneously improve the CO2 conversion rate and methanol selectivity of carbon dioxide hydrogenation catalysts, and to provide a carbon dioxide hydrogenation to methanol catalyst, its preparation method and application. This carbon dioxide hydrogenation to methanol catalyst contains copper-zinc bimetallic oxide and uses nitrogen-doped carbon materials to modify the copper-zinc bimetallic oxide, thereby significantly improving the catalytic activity and methanol selectivity of the carbon dioxide hydrogenation to methanol catalyst.
[0005] To achieve the above objectives, the present invention provides a catalyst for the hydrogenation of carbon dioxide to methanol, wherein the catalyst contains a copper-zinc bimetallic oxide, and the surface of the copper-zinc bimetallic oxide is modified with nitrogen-doped carbon material; based on the total weight of the catalyst, the content of the nitrogen-doped carbon material is 0.498-3.226 wt%.
[0006] Preferably, the weight ratio of the copper-zinc bimetallic oxide to the nitrogen-doped carbon material is 30~200:1; Preferably, in the copper-zinc bimetallic oxide, the molar ratio of copper to zinc is 0.25 to 1:1.
[0007] A second aspect of this invention provides a method for preparing a catalyst for the hydrogenation of carbon dioxide to methanol, the method comprising the following steps: (1) The solution containing copper and zinc sources is mixed with an alkaline substance and reacted. The resulting solid reaction product is then calcined to obtain copper-zinc bimetallic oxide. (2) The nitrogen-doped carbon material is ground and mixed with the copper-zinc bimetallic oxide, and then calcined; The weight ratio of the copper-zinc bimetallic oxide to the nitrogen-doped carbon material is 30~200:1; In step (2), the calcination conditions include a temperature of 300℃~500℃ and a time of 2h~6h.
[0008] Preferably, the preparation process of the nitrogen-doped carbon material includes: calcining an organic compound containing carbon and nitrogen elements in an inactive atmosphere.
[0009] Preferably, the calcination temperature is 450℃~600℃, and the calcination time is 2h~6h.
[0010] Preferably, the organic compound containing carbon and nitrogen elements is selected from at least one of melamine, pyridine, urea, and amino acids.
[0011] Preferably, the molar ratio of the copper source to the zinc source is 0.25 to 1:1, wherein the amounts of the copper source and the zinc source are both calculated as metal elements.
[0012] Preferably, the alkaline substance is selected from one or more of NaOH, Na2CO3, and ammonia water; Preferably, the ratio of the total molar amount of metal elements in the copper source and the zinc source to the molar amount of cations in the alkaline substance is 1:20 to 1:4, and more preferably 1:14 to 1:8.
[0013] Preferably, in step (1), the reaction conditions include: a temperature of 50°C to 80°C and a time of 1h to 4h.
[0014] Preferably, in step (1), the calcination conditions include: a temperature of 300℃~500℃, a heating rate of 1~8℃ / min, and a time of 2h~6h.
[0015] Preferably, in step (2), the heating rate during roasting is 1~8℃ / min.
[0016] Preferably, in step (2), the calcination is carried out in an inert gas.
[0017] Preferably, the flow rate of the inert gas is 30 mL / min to 100 mL / min.
[0018] A third aspect of the present invention provides a carbon dioxide hydrogenation to methanol catalyst prepared by the method described above.
[0019] The fourth aspect of this invention provides the application of the aforementioned carbon dioxide hydrogenation to methanol catalyst in the carbon dioxide hydrogenation to methanol reaction process.
[0020] The carbon dioxide hydrogenation to methanol catalyst of this invention modifies a copper-zinc bimetallic oxide using nitrogen-doped carbon material. This nitrogen-doped carbon material modulates the electronic structure of the copper-zinc bimetallic oxide, promoting not only the formation of the Cu / ZnO interface but also enhancing the interaction between Cu and ZnO, which is beneficial for methanol production. This results in a significant breakthrough in the activity of the carbon dioxide hydrogenation to methanol catalyst, exhibiting both high CO2 conversion and high methanol selectivity, thus solving the technical challenges currently faced by Cu / ZnO catalysts.
[0021] Under the set reaction conditions, the reactant gases used were a mixture of CO2 and H2, with a CO2 / H2 volume ratio of 1 / 3. The pressure was 3 MPa, and the mass hourly space velocity (GHSV) was 12000 mL·h. -1 ·g cat -1 Under the specified conditions, the carbon dioxide hydrogenation to methanol catalyst of this invention exhibits excellent activity for the carbon dioxide hydrogenation to methanol reaction. At a reaction temperature of 250°C, the CO2 conversion rate is 10.5%, and the methanol selectivity is as high as 82.3%, significantly higher than that of the unmodified CuO / ZnO catalyst. Furthermore, the methanol selectivity and yield of this carbon dioxide hydrogenation to methanol catalyst are also higher than most traditional Cu / ZnO catalysts. In addition, the carbon dioxide hydrogenation to methanol catalyst of this invention is prepared by thoroughly mechanically mixing copper-zinc bimetallic oxide with nitrogen-doped carbon material and then calcining it. The preparation process is relatively simple, and the prepared catalyst can further improve the reactivity of CO2 hydrogenation to methanol, especially the methanol selectivity.
[0022] Compared to currently reported Cu / ZnO catalysts, the carbon dioxide hydrogenation to methanol catalyst of this invention achieves a significant breakthrough in the activity of the CO2 hydrogenation to methanol reaction. When the CO2 conversion rate is 10.5%, the methanol selectivity can still be maintained at 82.3%. Typically, under similar reaction conditions, for conventional Cu / ZnO catalysts, when the CO2 conversion rate exceeds 10%, the methanol selectivity rapidly drops below 75%, and the methanol formation activity is significantly lower than that of the carbon dioxide hydrogenation to methanol catalyst described in this invention. Attached Figure Description
[0023] Figure 1This is a graph showing the change in CO2 conversion rate of the catalysts prepared in Example 1 and Comparative Example 1 as a function of reaction temperature. Figure 2 This is a graph showing the methanol selectivity of the catalysts prepared in Example 1 and Comparative Example 1 as a function of reaction temperature. Detailed Implementation
[0024] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0025] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0026] The carbon dioxide hydrogenation to methanol catalyst of this invention contains a copper-zinc bimetallic oxide, and the surface of the copper-zinc bimetallic oxide is modified with nitrogen-doped carbon material. The nitrogen-doped carbon material used in this invention is not used as a support, but rather to modify the surface of the copper-zinc bimetallic oxide. This modulates the electronic structure of the copper-zinc bimetallic oxide surface, promoting not only the formation of the Cu / ZnO interface but also enhancing the interaction between CuO and ZnO, which is beneficial for methanol production. This increases the number of active sites on the catalyst and improves their catalytic activity, further enhancing the catalytic activity of the carbon dioxide hydrogenation to methanol catalyst, resulting in a catalyst with both high CO2 conversion and methanol selectivity.
[0027] In this invention, based on the total weight of the catalyst, the content of the nitrogen-doped carbon material is 0.498-3.226 wt%, preferably 0.99-1.96 wt%. When the content of the nitrogen-doped carbon material is too high or too low, it will lead to a decrease in the catalytic activity of the carbon dioxide hydrogenation to methanol catalyst, and a reduction in CO2 conversion rate and methanol selectivity.
[0028] In some preferred embodiments, to further enhance the catalytic activity of the carbon dioxide hydrogenation to methanol catalyst, the weight ratio of the copper-zinc bimetallic oxide to the nitrogen-doped carbon material is limited to 30-200:1, preferably 50-100:1. Specifically, the weight ratio of the copper-zinc bimetallic oxide to the nitrogen-doped carbon material can be 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 130:1, 140:1, 150:1, 160:1, 170:1, 180:1, 190:1, or 200:1.
[0029] In some preferred embodiments, the molar ratio of copper to zinc in the copper-zinc bimetallic oxide is 0.25 to 1:1, preferably 0.35 to 0.5:1. Specifically, the molar ratio of copper to zinc can be 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, or 1:1.
[0030] This invention further provides a method for preparing a catalyst for the hydrogenation of carbon dioxide to methanol, the method comprising the following steps: (1) The solution containing copper and zinc sources is mixed with an alkaline substance and reacted. The resulting solid reaction product is then calcined to obtain copper-zinc bimetallic oxide. (2) The nitrogen-doped carbon material is ground and mixed with the copper-zinc bimetallic oxide, and then calcined.
[0031] In the method described in this invention, the weight ratio of the copper-zinc bimetallic oxide to the nitrogen-doped carbon material is 30-200:1, preferably 50-100:1. By limiting the ratio of the two, the catalytic activity and methanol selectivity of the prepared carbon dioxide hydrogenation to methanol catalyst can be guaranteed to be higher. When the ratio of the two is not within the range limited by this invention, the activity of the prepared catalyst will be reduced, affecting the methanol selectivity. Specifically, the weight ratio of the copper-zinc bimetallic oxide to the nitrogen-doped carbon material can be 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 130:1, 140:1, 150:1, 160:1, 170:1, 180:1, 190:1, or 200:1.
[0032] In some embodiments, the preparation process of the nitrogen-doped carbon material includes calcining an organic compound containing carbon and nitrogen elements in an inactive atmosphere. The method described in this invention is not limited to a specific type of organic compound containing carbon and nitrogen elements; for example, it may be at least one of melamine, pyridine, urea, and amino acids.
[0033] In the method described in this invention, the inactive gas refers to a gas that does not participate in the reaction during the reaction process. In a specific embodiment, the inactive gas is selected from at least one of nitrogen and an inert gas (such as argon). The conditions for calcining organic compounds containing carbon and nitrogen elements in an inactive atmosphere include: a temperature of 450℃~600℃ and a time of 2h~6h.
[0034] In some preferred embodiments, the molar ratio of the copper source to the zinc source is 0.25 to 1:1, preferably 0.35 to 0.5:1, wherein the amounts of the copper source and the zinc source are both calculated as metallic elements. Specifically, the molar ratio of the copper source to the zinc source can be 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, or 1:1.
[0035] In the method described in this invention, in step (1), the alkaline substance is used to precipitate copper ions and zinc ions in the copper source and the zinc source. In this invention, the specific composition of the alkaline substance is not limited. For example, the alkaline substance can be selected from one or more of NaOH, Na2CO3 and ammonia water.
[0036] In some preferred embodiments, the ratio of the total molar amount of metal elements in the copper source and the zinc source to the molar amount of cations in the alkaline substance is 1:4 to 1:20, preferably 1:8 to 1:14. Specifically, the total molar amount of metal elements in the copper source and the zinc source refers to the sum of the molar amounts of copper and zinc in the copper source, and the molar amount of cations in the alkaline substance refers to the molar amount of cations contained in the alkaline substance. The ratio of the total molar amount of metal elements in the copper source and the zinc source to the molar amount of cations in the alkaline substance can be 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18, or 1:20.
[0037] In some embodiments, the reaction conditions in step (1) include: a temperature of 50°C to 80°C and a time of 1h to 4h.
[0038] In some embodiments, the calcination conditions in step (1) include: a temperature of 300°C to 500°C, a heating rate of 1 to 8°C / min, and a time of 2 to 6 hours.
[0039] In some embodiments, the specific operation process of step (1) includes: mixing a solution containing copper and zinc sources with an alkaline substance to react, filtering the reacted material to separate the solid reaction product, washing and drying the solid reaction product, and then calcining the dried solid reaction product to obtain copper-zinc bimetallic oxide.
[0040] In the method described in this invention, in step (2), by grinding and mixing the nitrogen-doped carbon material with the copper-zinc bimetallic oxide, it can be ensured that the prepared catalyst has excellent CO2 conversion rate and methanol selectivity.
[0041] In the method described in this invention, the calcination temperature after grinding and mixing the nitrogen-doped carbon material with the copper-zinc bimetallic oxide in step (2) is particularly important for the catalytic activity and methanol selectivity of the prepared carbon dioxide hydrogenation to methanol catalyst. Too high or too low a calcination temperature will reduce the activity of the prepared carbon dioxide hydrogenation to methanol catalyst. If the calcination temperature is too low, the nitrogen-doped carbon material and the copper-zinc bimetallic oxide will not be in close contact and cannot interact; if the calcination temperature is too high, the Cu species particle size will increase, leading to a decrease in the specific surface area of active Cu, both of which are detrimental to methanol production. Specifically, in step (2), the calcination conditions include: a temperature of 300℃~500℃, preferably 350℃~450℃, and a time of 2h~6h, preferably 3h~5h. Specifically, the calcination temperature can be 300℃, 350℃, 400℃, 450℃, or 500℃; the calcination time can be 2h, 3h, 4h, 5h, or 6h.
[0042] In some embodiments, in step (2), the heating rate during calcination is 1~8℃ / min.
[0043] In some embodiments, in step (2), the calcination is carried out in an inert gas, which may be nitrogen and / or argon. Specifically, during calcination, the flow rate of the inert gas may be 30 mL / min to 100 mL / min.
[0044] The carbon dioxide hydrogenation to methanol catalyst prepared by the above method exhibits excellent catalytic performance, with both high CO2 conversion and methanol selectivity, at a pressure of 3 MPa and a mass hourly space velocity (GHSV) of 12000 mL·h. -1 ·g cat -1Under the specified conditions, the carbon dioxide hydrogenation to methanol catalyst prepared in this invention exhibits excellent activity for the carbon dioxide hydrogenation to methanol reaction. At a reaction temperature of 250℃, the CO2 conversion rate is 10.5%, and the methanol selectivity is as high as 82.3%, significantly higher than that of existing Cu / ZnO catalysts. Furthermore, the methanol selectivity and yield of the carbon dioxide hydrogenation to methanol catalyst prepared in this invention are also higher than most traditional Cu / ZnO catalysts. In addition, the carbon dioxide hydrogenation to methanol catalyst of this invention is prepared by thoroughly mechanically mixing copper-zinc bimetallic oxide with CN followed by calcination, resulting in a relatively simple preparation process. This process can further improve the reactivity of CO2 hydrogenation to methanol, especially the methanol selectivity, providing strong support for technological advancements in related fields.
[0045] The present invention will be described in detail below through embodiments, but the scope of protection of the present invention is not limited thereto.
[0046] Example 1 (1) Weigh 1g of melamine and put it into a quartz boat. Place it in a tube furnace and heat it to 550℃ at a flow rate of 50mL / min and keep it at that temperature for 4h. After cooling to room temperature under N2 atmosphere, N-doped C material is obtained, which is denoted as CN material. (2) Weigh 1.1407 g of Cu(NO3)2·3H2O and 3.1842 g of Zn(NO3)2·6H2O, dissolve them in 20 mL of deionized water, and stir rapidly until the solution is clear and transparent, with a Cu / Zn molar ratio of 3 / 7. Prepare a 1.5 mol / L Na2CO3 precipitant solution. Stir and heat the mixed solution of Cu(NO3)2 and Zn(NO3)2 to 65 °C, and then slowly add 50 mL of the 1.5 mol / L Na2CO3 precipitant solution to the mixed solution. At this time, the Na in the precipitant will be less than 100 g. + The molar ratio of the metal element (Cu+Zn) in the metal salts (Cu(NO3)2 and Zn(NO3)2) is 10. The mixture is heated and stirred in a constant temperature oil bath at 65℃ for 2 hours to ensure complete precipitation. After the reaction is complete, the mixture is filtered, washed three times with 500 mL of deionized water, and dried in a forced-air drying oven at 105℃ for 12 hours. After drying, the sample is removed, ground into powder, and calcined in a muffle furnace at 400℃ for 4 hours to obtain the copper-zinc bimetallic oxide CuO / ZnO, wherein the molar ratio of Cu / Zn in this bimetallic oxide is 3 / 7. (3) Weigh 0.0072g of CN material and 0.50g of copper-zinc bimetallic oxide CuO / ZnO and put them into a mortar. Stir and grind them thoroughly and mechanically mix them to ensure uniform mixing. Collect the mixture into a quartz boat and place it in a tube furnace. Under N2 atmosphere, heat the mixture to 400℃ at 5℃ / min and calcine for 3h. The N2 flow rate is 50mL / min. The catalyst for the hydrogenation of carbon dioxide to methanol is obtained. The mass ratio of CN material to copper-zinc bimetallic oxide CuO / ZnO is 1 / 70. The content of CN material in the catalyst is 1.41wt%. This catalyst for the hydrogenation of carbon dioxide to methanol is named CuO / ZnO / CN-1 catalyst.
[0047] Example 2 (1) Weigh 1g of melamine and put it into a quartz boat. Place it in a tube furnace and heat it to 550℃ at a flow rate of 50mL / min and keep it at that temperature for 4h. After cooling to room temperature under N2 atmosphere, N-doped C material is obtained, which is denoted as CN material. (2) Weigh 1.1407 g of Cu(NO3)2·3H2O and 3.1842 g of Zn(NO3)2·6H2O, dissolve them in 20 mL of deionized water, and stir rapidly until the solution is clear and transparent, with a Cu / Zn molar ratio of 3 / 7. Prepare a 1.5 mol / L Na2CO3 precipitant solution. Stir and heat the mixed solution of Cu(NO3)2 and Zn(NO3)2 to 65 °C, and then slowly add 50 mL of the 1.5 mol / L Na2CO3 precipitant solution to the mixed solution. At this time, the Na in the precipitant will be less than 100 g. + The molar ratio of the metal element (Cu+Zn) in the metal salts (Cu(NO3)2 and Zn(NO3)2) is 10. The mixture is heated and stirred in a constant temperature oil bath at 65℃ for 2 hours to ensure complete precipitation. After the reaction is complete, the mixture is filtered, washed three times with 500 mL of deionized water, and dried in a forced-air drying oven at 105℃ for 12 hours. After drying, the sample is removed, ground into powder, and calcined in a muffle furnace at 400℃ for 4 hours to obtain the copper-zinc bimetallic oxide CuO / ZnO, wherein the molar ratio of Cu / Zn in this bimetallic oxide is 3 / 7. (3) Weigh 0.0025g of CN material and 0.50g of copper-zinc bimetallic oxide CuO / ZnO and put them into a mortar. Stir and grind them thoroughly and mechanically mix them to ensure uniform mixing. Collect the mixture into a quartz boat and place it in a tube furnace. Calcine it at 400℃ for 3h under N2 atmosphere at a rate of 5℃ / min. The N2 flow rate is 50mL / min. The catalyst for the hydrogenation of carbon dioxide to methanol is obtained. The mass ratio of CN material to copper-zinc bimetallic oxide CuO / ZnO is 1 / 200. The content of CN material in the catalyst is 0.498wt%. This catalyst for the hydrogenation of carbon dioxide to methanol is named CuO / ZnO / CN-2 catalyst.
[0048] Example 3 (1) Weigh 1g of melamine and put it into a quartz boat. Place it in a tube furnace and heat it to 550℃ at a flow rate of 50mL / min and keep it at that temperature for 4h. After cooling to room temperature under N2 atmosphere, N-doped C material is obtained, which is denoted as CN material. (2) Weigh 1.1407 g of Cu(NO3)2·3H2O and 3.1842 g of Zn(NO3)2·6H2O, dissolve them in 20 mL of deionized water, and stir rapidly until the solution is clear and transparent, with a Cu / Zn molar ratio of 3 / 7. Prepare a 1.5 mol / L Na2CO3 precipitant solution. Stir and heat the mixed solution of Cu(NO3)2 and Zn(NO3)2 to 65 °C, and then slowly add 50 mL of the 1.5 mol / L Na2CO3 precipitant solution to the mixed solution. At this time, the Na in the precipitant will be less than 100 g. + The molar ratio of the metal element (Cu+Zn) in the metal salts (Cu(NO3)2 and Zn(NO3)2) is 10. The mixture is heated and stirred in a constant temperature oil bath at 65℃ for 2 hours to ensure complete precipitation. After the reaction is complete, the mixture is filtered, washed three times with 500 mL of deionized water, and dried in a forced-air drying oven at 105℃ for 12 hours. After drying, the sample is removed, ground into powder, and calcined in a muffle furnace at 400℃ for 4 hours to obtain the copper-zinc bimetallic oxide CuO / ZnO, wherein the molar ratio of Cu / Zn in this bimetallic oxide is 3 / 7. (3) Weigh 0.0167g of CN material and 0.50g of copper-zinc bimetallic oxide CuO / ZnO and put them into a mortar. Stir and grind them thoroughly and mechanically mix them to ensure uniform mixing. Collect the mixture into a quartz boat and place it in a tube furnace. Calcine it at 400℃ for 3h under N2 atmosphere at a rate of 5℃ / min. The N2 flow rate is 50mL / min. The catalyst for the hydrogenation of carbon dioxide to methanol is obtained. The mass ratio of CN material to copper-zinc bimetallic oxide CuO / ZnO is 1 / 30. The content of CN material in the catalyst is 3.23wt%. This catalyst for the hydrogenation of carbon dioxide to methanol is named CuO / ZnO / CN-3 catalyst.
[0049] Example 4 (1) Weigh 1g of melamine and put it into a quartz boat. Place it in a tube furnace and heat it to 550℃ at a flow rate of 50mL / min and keep it at that temperature for 4h. After cooling to room temperature under N2 atmosphere, N-doped C material is obtained, which is denoted as CN material. (2) Weigh 1.1407 g of Cu(NO3)2·3H2O and 3.1842 g of Zn(NO3)2·6H2O, dissolve them in 20 mL of deionized water, and stir rapidly until the solution is clear and transparent, with a Cu / Zn molar ratio of 3 / 7. Prepare a 1.5 mol / L Na2CO3 precipitant solution. Stir and heat the mixed solution of Cu(NO3)2 and Zn(NO3)2 to 65 °C, and then slowly add 50 mL of the 1.5 mol / L Na2CO3 precipitant solution to the mixed solution. At this time, the Na in the precipitant will be less than 100 g. + The molar ratio of the metal element (Cu+Zn) in the metal salts (Cu(NO3)2 and Zn(NO3)2) is 10. The mixture is heated and stirred in a constant temperature oil bath at 65℃ for 2 hours to ensure complete precipitation. After the reaction is complete, the mixture is filtered, washed three times with 500 mL of deionized water, and dried in a forced-air drying oven at 105℃ for 12 hours. After drying, the sample is removed, ground into powder, and calcined in a muffle furnace at 400℃ for 4 hours to obtain the copper-zinc bimetallic oxide CuO / ZnO, wherein the molar ratio of Cu / Zn in this bimetallic oxide is 3 / 7. (3) Weigh 0.0072g of CN material and 0.50g of copper-zinc bimetallic oxide CuO / ZnO and put them into a mortar. Stir and grind them thoroughly and mechanically mix them to ensure uniform mixing. Collect the mixture into a quartz boat and place it in a tube furnace. Under N2 atmosphere, heat the mixture to 300℃ at 5℃ / min and calcine for 3h. The N2 flow rate is 50mL / min. The catalyst for the hydrogenation of carbon dioxide to methanol is obtained. The mass ratio of CN material to copper-zinc bimetallic oxide CuO / ZnO is 1 / 70. The content of CN material in the catalyst is 1.41wt%. The catalyst for the hydrogenation of carbon dioxide to methanol is named CuO / ZnO / CN-4 catalyst.
[0050] Example 5 (1) Weigh 1g of melamine and put it into a quartz boat. Place it in a tube furnace and heat it to 550℃ at a flow rate of 50mL / min and keep it at that temperature for 4h. After cooling to room temperature under N2 atmosphere, N-doped C material is obtained, which is denoted as CN material. (2) Weigh 1.1407 g of Cu(NO3)2·3H2O and 3.1842 g of Zn(NO3)2·6H2O, dissolve them in 20 mL of deionized water, and stir rapidly until the solution is clear and transparent, with a Cu / Zn molar ratio of 3 / 7. Prepare a 1.5 mol / L Na2CO3 precipitant solution. Stir and heat the mixed solution of Cu(NO3)2 and Zn(NO3)2 to 65 °C, and then slowly add 50 mL of the 1.5 mol / L Na2CO3 precipitant solution to the mixed solution. At this time, the Na in the precipitant will be less than 100 g. +The molar ratio of the metal element (Cu+Zn) in the metal salts (Cu(NO3)2 and Zn(NO3)2) is 10. The mixture is heated and stirred in a constant temperature oil bath at 65℃ for 2 hours to ensure complete precipitation. After the reaction is complete, the mixture is filtered, washed three times with 500 mL of deionized water, and dried in a forced-air drying oven at 105℃ for 12 hours. After drying, the sample is removed, ground into powder, and calcined in a muffle furnace at 400℃ for 4 hours to obtain the copper-zinc bimetallic oxide CuO / ZnO, wherein the molar ratio of Cu / Zn in this bimetallic oxide is 3 / 7. (3) Weigh 0.0072g of CN material and 0.50g of copper-zinc bimetallic oxide CuO / ZnO and put them into a mortar. Stir and grind them thoroughly and mechanically mix them to ensure uniform mixing. Collect the mixture into a quartz boat and place it in a tube furnace. Calcine it at 500℃ for 3h under N2 atmosphere with a heating rate of 5℃ / min and a N2 flow rate of 50mL / min to obtain a carbon dioxide hydrogenation to methanol catalyst. The mass ratio of CN to Cu / ZnO is 1 / 70 and the content of CN material in the catalyst is 1.41wt%. This carbon dioxide hydrogenation to methanol catalyst is named CuO / ZnO / CN-5 catalyst.
[0051] Comparative Example 1 Weigh 1.1407 g of Cu(NO3)2·3H2O and 3.1842 g of Zn(NO3)2·6H2O, dissolve them in 20 mL of deionized water, and stir rapidly until the solution is clear and transparent, with a Cu / Zn molar ratio of 3 / 7. Prepare a 1.5 mol / L Na2CO3 precipitant solution. Heat the mixed solution of Cu(NO3)2 and Zn(NO3)2 to 65 °C, and then slowly add 50 mL of the 1.5 mol / L Na2CO3 precipitant solution dropwise to the mixed solution. At this point, the Na content in the precipitant will decrease. + The molar ratio of the metal element (Cu+Zn) in the metal salts (Cu(NO3)2 and Zn(NO3)2) is 10. The mixture is heated and stirred in a constant temperature oil bath at 65℃ for 2 hours to ensure complete precipitation. After the reaction is complete, the mixture is filtered, washed three times with 500 mL of deionized water, and dried in a forced-air drying oven at 105℃ for 12 hours. After drying, the sample is removed, ground into powder, and calcined in a muffle furnace at 400℃ for 4 hours to obtain the copper-zinc bimetallic oxide CuO / ZnO. The molar ratio of Cu / Zn in this bimetallic oxide is 3 / 7, and it is designated as the CuO / ZnO catalyst.
[0052] Comparative Example 2 (1) Weigh 1g of melamine and put it into a quartz boat. Place it in a tube furnace and heat it to 550℃ at a flow rate of 50mL / min and keep it at that temperature for 4h. After cooling to room temperature under N2 atmosphere, N-doped C material is obtained, which is denoted as CN material. (2) Weigh 1.1407 g of Cu(NO3)2·3H2O and 3.1842 g of Zn(NO3)2·6H2O, dissolve them in 20 mL of deionized water, and stir rapidly until the solution is clear and transparent, with a Cu / Zn molar ratio of 3 / 7. Prepare a 1.5 mol / L Na2CO3 precipitant solution. Stir and heat the mixed solution of Cu(NO3)2 and Zn(NO3)2 to 65 °C, and then slowly add 50 mL of the 1.5 mol / L Na2CO3 precipitant solution to the mixed solution. At this time, the Na in the precipitant will be less than 100 g. + The molar ratio of the metal element (Cu+Zn) in the metal salts (Cu(NO3)2 and Zn(NO3)2) is 10. The mixture is heated and stirred in a constant temperature oil bath at 65℃ for 2 hours to ensure complete precipitation. After the reaction is complete, the mixture is filtered, washed three times with 500 mL of deionized water, and dried in a forced-air drying oven at 105℃ for 12 hours. After drying, the sample is removed, ground into powder, and calcined in a muffle furnace at 400℃ for 4 hours to obtain the copper-zinc bimetallic oxide CuO / ZnO, in which the molar ratio of Cu / Zn is 3 / 7. (3) Weigh 0.0333g of CN material and 0.50g of copper-zinc bimetallic oxide CuO / ZnO and put them into a mortar. Stir and grind them thoroughly and mechanically mix them to ensure uniform mixing. Collect the mixture into a quartz boat and place it in a tube furnace. Calcine the mixture at 400℃ for 3h under N2 atmosphere at a rate of 5℃ / min. The N2 flow rate is 50mL / min. The catalyst is obtained. The mass ratio of CN material to copper-zinc bimetallic oxide CuO / ZnO in the catalyst is 1 / 15. The content of CN material in the catalyst is 6.25wt%. It is called CuO / ZnO / CN-6 catalyst.
[0053] Comparative Example 3 (1) Weigh 1g of melamine and put it into a quartz boat. Place it in a tube furnace and heat it to 550℃ at a flow rate of 50mL / min and keep it at that temperature for 4h. After cooling to room temperature under N2 atmosphere, N-doped C material is obtained, which is denoted as CN material. (2) Weigh 1.1407 g of Cu(NO3)2·3H2O and 3.1842 g of Zn(NO3)2·6H2O, dissolve them in 20 mL of deionized water, and stir rapidly until the solution is clear and transparent, with a Cu / Zn molar ratio of 3 / 7. Prepare a 1.5 mol / L Na2CO3 precipitant solution. Stir and heat the mixed solution of Cu(NO3)2 and Zn(NO3)2 to 65 °C, and then slowly add 50 mL of the 1.5 mol / L Na2CO3 precipitant solution to the mixed solution. At this time, the Na in the precipitant will be less than 100 g. +The molar ratio of the metal element (Cu+Zn) in the metal salts (Cu(NO3)2 and Zn(NO3)2) is 10. Continue heating and stirring in a constant temperature oil bath at 65℃ for 2 hours to ensure complete precipitation. After the reaction is complete, filter, wash the product three times with 500 mL of deionized water, and dry in a forced-air drying oven at 105℃ for 12 hours. After drying, remove the sample, grind it into powder, and calcine it in a muffle furnace at 400℃ for 4 hours to obtain the copper-zinc bimetallic oxide CuO / ZnO, in which the molar ratio of Cu / Zn is 3 / 7. (3) Weigh 0.0072g of CN material and 0.50g of copper-zinc bimetallic oxide CuO / ZnO and put them into a mortar and stir and grind them thoroughly. Mechanically mix them to ensure uniform mixing. Collect them into a quartz boat and place them in a tube furnace. Calcine them at 200℃ for 3h under N2 atmosphere at a rate of 5℃ / min. The N2 flow rate is 50mL / min. The catalyst CuO / ZnO / CN is obtained. The mass ratio of CN material to copper-zinc bimetallic oxide CuO / ZnO in the catalyst is 1 / 70. The content of CN material in the catalyst is 1.41wt%. It is called CuO / ZnO / CN-7 catalyst.
[0054] Comparative Example 4 (1) Weigh 1g of melamine and put it into a quartz boat. Place it in a tube furnace and heat it to 550℃ at a flow rate of 50mL / min and keep it at that temperature for 4h. After cooling to room temperature under N2 atmosphere, N-doped C material is obtained, which is denoted as CN material. (2) Weigh 1.1407 g of Cu(NO3)2·3H2O and 3.1842 g of Zn(NO3)2·6H2O, dissolve them in 20 mL of deionized water, and stir rapidly until the solution is clear and transparent, with a Cu / Zn molar ratio of 3 / 7. Prepare a 1.5 mol / L Na2CO3 precipitant solution. Stir and heat the mixed solution of Cu(NO3)2 and Zn(NO3)2 to 65 °C, and then slowly add 50 mL of the 1.5 mol / L Na2CO3 precipitant solution to the mixed solution. At this time, the Na in the precipitant will be less than 100 g. + The molar ratio of the metal element (Cu+Zn) in the metal salts (Cu(NO3)2 and Zn(NO3)2) is 10. The mixture is heated and stirred in a constant temperature oil bath at 65℃ for 2 hours to ensure complete precipitation. After the reaction is complete, the mixture is filtered, washed three times with 500 mL of deionized water, and dried in a forced-air drying oven at 105℃ for 12 hours. After drying, the sample is removed, ground into powder, and calcined in a muffle furnace at 400℃ for 4 hours to obtain the copper-zinc bimetallic oxide CuO / ZnO, where the molar ratio of Cu / Zn is 3 / 7. (3) Weigh 0.0072g of CN material and 0.50g of copper-zinc bimetallic oxide CuO / ZnO and put them into a mortar. Stir and grind them thoroughly and mechanically mix them to ensure uniform mixing. Collect the mixture into a quartz boat and place it in a tube furnace. Calcine it at 600℃ for 3h under N2 atmosphere at a rate of 5℃ / min. The N2 flow rate is 50mL / min. The catalyst CuO / ZnO / CN is obtained. The mass ratio of CN material to copper-zinc bimetallic oxide CuO / ZnO in the catalyst is 1 / 70. The content of CN material in the catalyst is 1.41wt%. It is called CuO / ZnO / CN-8 catalyst.
[0055] Test Example 1 The catalysts prepared in the examples and comparative examples were tested for their performance in the carbon dioxide hydrogenation to methanol reaction.
[0056] Test method: The catalyst to be tested is tableted, crushed, and sieved (40-80 mesh). 0.1 g of the catalyst to be tested is weighed and mixed with an equal mass of quartz sand, then placed into a stainless steel reaction tube with an internal quartz tube (8 mm inner diameter). Before the reaction begins, the catalyst is pretreated under normal pressure by introducing high-purity H2 at a flow rate of 20 mL / min, raising the temperature to 250 °C for 2 h at a heating rate of 3 °C / min, and then cooling to 160 °C in an H2 atmosphere. The mixed feed gas (H2 / CO2 = 3 / 1, molar ratio) is then introduced into the fixed-bed reactor, and the reactor pressure is adjusted to 3 MPa, maintaining a gas hourly space velocity of 12000 mL / h. -1 g cat -1 The reaction time at each reaction temperature was maintained for 1 hour. The temperature range for catalyst activity evaluation was 160℃ to 340℃, with a heating rate of 3℃ / min. All pipelines from the reactor outlet to the six-way chromatographic valve were maintained at 150℃ to prevent product condensation. The product composition and content at different reaction temperatures were detected online using a gas chromatograph. The catalyst activity test results are shown in Table 1. The CO2 conversion rate of the catalysts prepared in Example 1 and Comparative Example 1 as a function of reaction temperature is shown in Table 1. Figure 1 As shown, the methanol selectivity of the catalysts prepared in Example 1 and Comparative Example 1 as a function of reaction temperature is as follows: Figure 2 As shown.
[0057] Table 1
[0058] Analysis of the data in Table 1 shows that as the mass ratio of CN material to CuO / ZnO increases from 1 / 200 to 1 / 15, both CO2 conversion and methanol selectivity exhibit a trend of first increasing and then decreasing. When the mass ratio of CN material to CuO / ZnO is 1 / 70, both CO2 conversion and methanol selectivity reach their peak values. For the optimal CuO / ZnO / CN-1 catalyst, when the CO2 conversion is 10.5%, the methanol selectivity still remains at 82.3%, significantly higher than that of CuO / ZnO alone. Figure 1 and Figure 2 This fully demonstrates that CuO / ZnO / CN-1 exhibits excellent methanol-generating activity in the carbon dioxide hydrogenation to methanol reaction. The introduction of CN not only promotes the formation of the Cu / ZnO interface but also enhances the interaction between Cu and ZnO, which is beneficial for methanol generation. However, excessively high CN content can induce the aggregation of Cu active species, leading to a reduction in hydrogenation active centers and hindering the carbon dioxide hydrogenation to methanol reaction, resulting in a significant decrease in CO2 conversion and methanol selectivity (CuO / ZnO / CN-6). Compared to CuO / ZnO, adding an appropriate amount of CN (CN to CuO / ZnO mass ratio of 1 / 200 to 1 / 30) can simultaneously improve both CO2 conversion and methanol selectivity, with CO2 conversion exceeding 9% and methanol selectivity exceeding 78%. Appropriate amounts of CN can enhance the methanol-generating activity of CuO / ZnO.
[0059] Furthermore, during the N2 atmosphere roasting process, when the roasting temperature was relatively low (200℃), the CO2 conversion rate and methanol selectivity were 8.5% and 74.1%, respectively; when the roasting temperature was too high (600℃), the CO2 conversion rate and methanol selectivity were 8.3% and 72.6%, respectively, both lower than CuO / ZnO alone. Too low a roasting temperature results in insufficient contact between CN and CuO / ZnO, preventing interaction; too high a roasting temperature leads to larger Cu species particle sizes, reducing the specific surface area of active Cu, both of which are detrimental to methanol formation.
[0060] In summary, when the mass ratio of CN to CuO / ZnO is in the range of 1 / 200 to 1 / 30 and the calcination temperature is maintained at 300 to 500℃, CN effectively promotes methanol formation. The CuO / ZnO / CN catalysts maintain relatively high methanol production activity in the process of carbon dioxide hydrogenation to methanol.
[0061] By controlling the CN material content and calcination temperature (the mass ratio of CN material to CuO / ZnO is 1 / 200~1 / 30, and the calcination temperature is 300~500℃), the CN material not only effectively promotes the formation of the Cu / ZnO interface, but also enhances the interaction between Cu and ZnO, improves the distribution of active sites and reaction efficiency, and is beneficial to methanol generation.
[0062] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A catalyst for the hydrogenation of carbon dioxide to methanol, characterized in that, The catalyst contains a copper-zinc bimetallic oxide, and the surface of the copper-zinc bimetallic oxide is modified with nitrogen-doped carbon material; based on the total weight of the catalyst, the content of the nitrogen-doped carbon material is 0.99-1.96 wt%. The weight ratio of the copper-zinc bimetallic oxide to the nitrogen-doped carbon material is 50~100:1; In the copper-zinc bimetallic oxide, the molar ratio of copper to zinc is 0.25 to 1:1; The preparation method of the carbon dioxide hydrogenation to methanol catalyst includes the following steps: (1) The solution containing copper and zinc sources is mixed with an alkaline substance and reacted. The resulting solid reaction product is then calcined to obtain copper-zinc bimetallic oxide. (2) The nitrogen-doped carbon material is ground and mixed with the copper-zinc bimetallic oxide, and then calcined; In step (2), the calcination conditions include a temperature of 300℃~500℃ and a time of 2h~6h.
2. The catalyst for carbon dioxide hydrogenation to methanol according to claim 1, characterized in that, The preparation process of the nitrogen-doped carbon material includes: calcining organic matter containing carbon and nitrogen elements in an inactive atmosphere.
3. The catalyst for carbon dioxide hydrogenation to methanol according to claim 2, characterized in that, The calcination temperature is 450℃~600℃, and the calcination time is 2h~6h.
4. The catalyst for carbon dioxide hydrogenation to methanol according to claim 2, characterized in that, The organic compound containing carbon and nitrogen elements is selected from at least one of melamine, pyridine, urea, and amino acids.
5. The catalyst for carbon dioxide hydrogenation to methanol according to claim 1, characterized in that, The molar ratio of the copper source to the zinc source is 0.25 to 1:1, wherein the amounts of the copper source and the zinc source are calculated as metal elements.
6. The catalyst for carbon dioxide hydrogenation to methanol according to claim 1, characterized in that, The alkaline substance is selected from one or more of NaOH, Na2CO3, and ammonia water.
7. The catalyst for carbon dioxide hydrogenation to methanol according to claim 1, characterized in that, The ratio of the total molar amount of metal elements in the copper source and the zinc source to the molar amount of cations in the alkaline substance is 1:20 to 1:
4.
8. The catalyst for carbon dioxide hydrogenation to methanol according to claim 1, characterized in that, The ratio of the total molar amount of metal elements in the copper source and the zinc source to the molar amount of cations in the alkaline substance is 1:14 to 1:
8.
9. The catalyst for carbon dioxide hydrogenation to methanol according to claim 1, characterized in that, In step (1), the reaction conditions include: a temperature of 50℃~80℃ and a time of 1h~4h.
10. The catalyst for the hydrogenation of carbon dioxide to methanol according to claim 1, characterized in that, In step (1), the calcination conditions include: a temperature of 300℃~500℃, a heating rate of 1~8℃ / min, and a time of 2h~6h.
11. The catalyst for carbon dioxide hydrogenation to methanol according to claim 1, characterized in that, In step (2), the heating rate during roasting is 1~8℃ / min.
12. The catalyst for carbon dioxide hydrogenation to methanol according to claim 1, characterized in that, In step (2), the calcination is carried out in an inert gas.
13. The catalyst for carbon dioxide hydrogenation to methanol according to claim 12, characterized in that, The flow rate of the inert gas is 30 mL / min to 100 mL / min.
14. The application of the carbon dioxide hydrogenation to methanol catalyst according to any one of claims 1-13 in the carbon dioxide hydrogenation to methanol reaction process.
Citation Information
Patent Citations
Catalyst for preparing methanol through carbon dioxide hydrogenation and preparation method thereof
CN111437862A